2018
DOI: 10.1007/s13205-018-1358-0
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal mushroom: boon for therapeutic applications

Abstract: Medicinal mushrooms are higher fungi with additional nutraceutical attributes having low fat content and a trans-isomer of unsaturated fatty acids along with high fibre content, triterpenes, phenolic compounds, sterols, eritadenine and chitosan. They are considered as the unmatched source of healthy foods and drugs. They have outstanding attractive taste, aroma and nutritional value, so are considered as functional food, which means they are beneficial to the body not only in terms of nutrition but also for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(96 citation statements)
references
References 101 publications
(105 reference statements)
0
77
0
4
Order By: Relevance
“…These present in mushrooms belong to the 1,3-β-glucan family and have anti-tumor activity that operates by enhancing and blocking cellular immune pathways. [69,70] The content of water-soluble polysaccharides in T. indicum from different regions ranges from 70.23 to 115.24 mg/g dw ( Table 4). Tibetan truffles possess the highest polysaccharide content, followed by truffles from Hebei, Gongshan, Liaoning and Qujing.…”
Section: Polysaccharidesmentioning
confidence: 99%
“…These present in mushrooms belong to the 1,3-β-glucan family and have anti-tumor activity that operates by enhancing and blocking cellular immune pathways. [69,70] The content of water-soluble polysaccharides in T. indicum from different regions ranges from 70.23 to 115.24 mg/g dw ( Table 4). Tibetan truffles possess the highest polysaccharide content, followed by truffles from Hebei, Gongshan, Liaoning and Qujing.…”
Section: Polysaccharidesmentioning
confidence: 99%
“…Medicinal mushrooms are rich sources of pharmacologically active compounds (Chaturvedi et al , ). Ganoderma lucidum , a traditional medicinal mushroom, has been used to improve health and longevity in China for several millennia (Hsu and Cheng, ).…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal mushrooms are rich sources of pharmacologically active compounds (Chaturvedi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mushrooms are emerging as promising sources for naturally occurring novel bioactive compounds, as many studies have found their bioactive properties, including anti-cancer, anti-diabetic, anti-obesity, and hypocholesterolemic effects [30]. These beneficial effects of mushrooms on human health are attributed to a large number of secondary metabolites in their extracts.…”
Section: Discussionmentioning
confidence: 99%